Silencing of circCYP51A1 represses cell progression and glycolysis by regulating miR-490-3p/KLF12 axis in osteosarcoma under hypoxia - Jian Yang; Zhiwei Liu; Ben Liu; Lishan Sun (Journal of Bone Oncology, 2022)
Background: Hypoxia is a key characteristic of osteosarcoma (OS). Increasing data suggested that circular RNA (circRNAs) were involve in the progression of cancers and the regulation of hypoxia, including OS. This study aims to examine the biological mechanism of circRNA cytochrome P450 family 51 subfamily A member 1 (circCYP51A1) in OS under hypoxia. Methods: The expression levels of circCYP51A1, microRNA-490-3p (miR-490-3p) and kruppel-like factor 12 (KLF12) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) in OS tissues and cells. Cell proliferation, migration and invasion were determined by colony formation assay and transwell assay. Lactate production and glucose consumption in OS cells were measured by using lactate assay kit and glucose assay kit, respectively. Western blot assay and immunohistochemistry assay were used to test protein levels. The associated relationship between miR-490-3p and circCYP51A1 or KLF12 was predicted using Starbase or DIANA online database and verified by dual-luciferase reporter assay. The xenograft model was used to explore the role of circCYP51A1 in vivo. Results: CircCYP51A1 and KLF12 expression were dramatically increased, whereas miR-490-3p was decreased in OS cells under hypoxia condition. Deficiency of circCYP51A1 hindered hypoxia-induced cell proliferation, migration, invasion and glycolysis in OS cells. CircCYP51A1 enhanced KLF12 expression by sponging miR-490-3p. MiR-490-3p inhibitor weakened the inhibition effect of circCYP51A1 knockdown on the progression of OS under hypoxia. Besides, overexpression of miR-490-3p inhibited cell progression of OS under hypoxia condition, while the effects were attenuated by KLF12 overexpression. Importantly, knockdown of circCYP51A1 inhibited tumor growth in vivo. Conclusion: CircCYP51A1 mediated cell proliferation, migration, invasion and glycolysis by regulating miR-490-3p/KLF12 axis in OS cells under hypoxia condition.